A New Mathematical Model for the Performance of Axial Magnetic Filters. (1984) - Collan, H. K.; Kokkala, M. A.; Toikka, O. E.
Abstract : A mathematical model to describe the macroscopic behaviour of an axial magnetic filter is developed. The model takes into account the long range of absorption forces. Partial mixing of the particles in the fluid is included by introducing the concept of "mixing length". Behaviour of an axial filter under different conditions is numerically simulated. Experiments with colloidal ferrite particles indicate that for an axial filter composed of 12 μm steel wires with a packing factor of 4.8% the mixing length is of the order of 4 mm.